Recombinant activated factor VII in the treatment of bleeds and for the prevention of surgery-related bleeding in congenital haemophilia with inhibitors. (June 2015) - Santagostino, Elena; Escobar, Miguel; Ozelo, Margareth; Solimeno, Luigi; Arkhammar, Per; Lee, Hye Youn; Rosu, Gabriela; Giangrande, Paul
Abstract: The availability of recombinant activated factor VII (rFVIIa, eptacog alfa activated) has greatly advanced the care of patients with haemophilia A or B who have developed inhibitors against the infused replacement factor. Recombinant FVIIa is licensed for the on-demand treatment of bleeding episodes and the prevention of bleeding in surgery or invasive procedures in patients with congenital haemophilia with inhibitors. This article attempts to review in detail the extensive evidence of rFVIIa in congenital haemophilia patients with inhibitors. Patients with acute bleeding episodes are best treated on demand at home, to achieve the short- and long-term benefits of rapid bleed control. Key prospective studies have shown that rFVIIa achieves consistently high efficacy rates in the management of acute (including joint) bleeds in inhibitor patients in the home treatment setting. Substantial post-approval data from key registries also support the on-demand efficacy profile of rFVIIa established by the prospective clinical trials. The availability of rFVIIa has allowed major surgery to become a reality for inhibitor patients. Studies in key surgery, including orthopaedic procedures, have found that rFVIIa provides consistently high efficacy rates. Importantly, the wealth of data does not raise any unexpected safety concerns surrounding rFVIIa use; this is likely because rFVIIa is a recombinant product with a localised mechanism of action at the site of vascular injury. In summary, rFVIIa is established as an effective and well-tolerated first-line treatment for on-demand bleeding control and bleed prevention during minor and major (including elective orthopaedic) surgery in inhibitor patients. Use of rFVIIa has been a major step towards narrowing the gap in outcomes between inhibitor patients and non-inhibitor patients.